2011
DOI: 10.1021/ie201734u
|View full text |Cite
|
Sign up to set email alerts
|

Explosions of Syngas/CO2 Mixtures in Oxygen-Enriched Air

Abstract: Most of the scientific works on syngas combustion deal with dry air as oxidizer, whereas very few studies have been carried out on syngas combustion in oxygen-enriched air (i.e., oxy-combustion). In this work, the explosion behavior (peak pressure and burning velocity) for H 2 /CO/O 2 /N 2 /CO 2 mixtures has been evaluated experimentally and numerically, for different H 2 /CO ratios, fuel (H 2 +CO) concentrations with respect to O 2 , molar percentages of CO 2 , and for values of the oxygen-enrichment factor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…More recently, we have found a similar behavior during closed vessel explosion tests for CH 4 /O 2 /N 2 /CO 2 [13e15] and H 2 /CO/O 2 /N 2 /CO 2 [8,16] mixtures. In particular, a transition has been observed e with increasing oxygen content e from deflagration to an anomalous regime characterized by oscillations and over-adiabatic peaks in pressure time histories.…”
Section: Introductionsupporting
confidence: 59%
“…More recently, we have found a similar behavior during closed vessel explosion tests for CH 4 /O 2 /N 2 /CO 2 [13e15] and H 2 /CO/O 2 /N 2 /CO 2 [8,16] mixtures. In particular, a transition has been observed e with increasing oxygen content e from deflagration to an anomalous regime characterized by oscillations and over-adiabatic peaks in pressure time histories.…”
Section: Introductionsupporting
confidence: 59%
“…A number of analytical and experimental studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have demonstrated the benefits of using oxygen enriched combustion in diesel engines. The results of all these investigation show a considerable decrease in unburned hydrocarbon, carbon monoxide emissions and smoke while oxides of nitrogen emissions increased pro-rata with the oxygen added.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [16] compared the combustion and emission characteristics of oxygenated fuel and raw oxygen added into the intake air and found that the combustion characteristics of hydrocarbon fuel enhanced by supplying extra oxygen as it increases the flame velocity, flame temperature, lean flammability limit, flame stability, and available energy. Salzano et al [14] and Cammarota et al [4] report that, increase in flame velocity and flame temperature can lead to a flame propagation which is not deflagration but it is combustion induced rapid phase transition. An increased laminar burning velocity due to oxygen enrichment leads to increase in maximum pressure and rate of pressure rise as explained by Di Benedetto et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the increase of O 2 content promoted the laminar propagation velocity and expanded the flammable range of CH 4 . Salzano et al 11 and Xu et al 12 studied the explosive characteristics of syngas and hydrous bioethanol in oxygen-enriched air conditions. Results show that the rising oxygen fraction promoted the deflagration index and explosive pressure.…”
Section: Introductionmentioning
confidence: 99%